WORKPLACE SMOKING POLICIES OF RHODE ISLAND EMPLOYERS - BUECHNER,JS; HANSON,DK; MATYAS,BT; VANDERSLICE,RR; WATERS,WJ (Tufts Archival Research Center, 2007)
Report on workplace smoking policies in Rhode Island. Finds that non-manufacturing facilities and larger work places have less restrictive smoking policies. Asserts that findings in Rhode Island are similar to those in the rest of the country. Includes charts of results.